Nurturing urban innovation and knowledge in the ongoing COVID-19 world - Banwari Mittal; Arch G. Woodside (Journal of Innovation & Knowledge (JIK), 2022)
Amidst the catastrophe of COVID-19, segments of the population globally experienced changes in their perspectives on life and the desire to live a more fulfilling life. The study here examines this emergent trend with secondary data available as published survey reports and personal observations using the inductive-reflective method of understanding and theorizing. The findings support the identification of five facets of this new mindset, namely, rise in altruism, growing community-mindedness, increasing focus on health and financial security, searching for work-life balance, and increasing experiences with nature. To channel this emergent mindset, this study proposes five categories of urban innovations: (1) revival of neighborhoods; (2) expansion of parks and nature; (3) investment in urban transportation and greenspaces, (4) incentivizing entrepreneurs for ecology and local 'maker economy,' and (5) staging community projects for collective good. The study describes the benefits of these innovations to general population and sets an agenda for urban planners, city managers, and social agencies as citizens begin their ongoing COVID lives. The study closes by advancing ten research proposals for future social science contributions in innovation and knowledge
Keywords: 650; COVID-19; altruism; community building; innovations in public projects; urban management